Multielement taxonomy, biostratigraphy, and paleoecology of late Triassic conodonts from the Mamonia Complex, southwestern Cyprus - Ryley, C. Christopher (Charles Christopher), 1961- (1987)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1987. Earth Sciences Bibliography: leaves 135-155.